A Fluorogenic Assay: Analysis of Chemical Modification of Lysine and Arginine to Control Proteolytic Activity of Trypsin - Kunal N. More; Tae-Hwan Lim; Julie Kang; Dong-Jo Chang (Molecules, 2021)
The chemical modification of amino acids plays an important role in the modulation of proteins or peptides and has useful applications in the activation and stabilization of enzymes, chemical biology, shotgun proteomics, and the production of peptide-based drugs. Although chemoselective modification of amino acids such as lysine and arginine via the insertion of respective chemical moieties as citraconic anhydride and phenyl glyoxal is important for achieving desired application objectives and has been extensively reported, the extent and chemoselectivity of the chemical modification of specific amino acids using specific chemical agents (blocking or modifying agents) has yet to be sufficiently clarified owing to a lack of suitable assay methodologies. In this study, we examined the utility of a fluorogenic assay method, based on a fluorogenic tripeptide substrate (FP-AA1-AA2-AA3) and the proteolytic enzyme trypsin, in determinations of the extent and chemoselectivity of the chemical modification of lysine or arginine. As substrates, we used two fluorogenic tripeptide probes, MeRho-Lys-Gly-Leu(Ac) (lysine-specific substrate) and MeRho-Arg-Gly-Leu(Ac) (arginine-specific substrate), which were designed, synthesized, and evaluated for chemoselective modification of specific amino acids (lysine and arginine) using the fluorogenic assay. The results are summarized in terms of half-maximal inhibitory concentrations (IC50) for the extent of modification and ratios of IC50 values (IC50arginine/IC50lysine and IC50lysine/IC50arginine) as a measure of the chemoselectivity of chemical modification for amino acids lysine and arginine. This novel fluorogenic assay was found to be rapid, precise, and reproducible for determinations of the extent and chemoselectivity of chemical modification.